Analysing Temporal and Spatial Changes in Land Cover: the Case of Drahna Forest Subdistrict Directorate - Kaptan, Sinan; Durkaya, Ali; Kaptan, Sinan; Durkaya, Ali (Kastamonu Univ, 2019)
Aim of study: In this study, changes in land cover and land use from designing forest management plans within a plan unit up until today in the field of study are analysed under various categories. Field of study: Drahna Forest Subdistrict Directorate (FSD) under Ulus Forest Operation Directorate (FOD) of Zonguldak Regional Directorate of Forestry (RDF) was selected as the field of this study Material and Method: Forest management plans and forest cover type maps for the related plan unit were utilized in the study. Forest cover type maps for the years 1967-1986 and 1986-2005 were digitized by using Geographical Information System tool ArcGIS version 10.4, whereas forest cover type map for the years 2006-2024 was obtained digitized from the relevant authority. Results: It was found that there was an increase of 227.6 ha in forest land in addition to a decrease of 227.6 ha in non-forest land between 1967 and 2006. It was also determined that there was a decrease of 2,295.33 ha in sparse forest land (with less than 10% canopy closure) whereas an increase of 2,523 ha in productive forest land (canopy closure above 11%). Further, a decrease of 369.91 ha in agricultural land in contrast with an increase of 36.69 ha in treeless forest land (TFL) and of 105.62 ha in settlement land were observed as well in non-forest lands. Emphasis of study: Within a period of 40 years between 1967 and 2006, immigration led to decreases in agricultural land and increases in forest land within the field of this study.
Analysing Temporal and Spatial Changes in Land Cover: the Case of Drahna Forest Subdistrict Directorate
Keywords: Land Use; Land Cover; Geographical Information Systems; Forest Management; Temporal And Spatial Change